A systematic review of overlapping microRNA patterns in systemic sclerosis and idiopathic pulmonary fibrosis. (17th May 2017) - Bagnato, Gianluca; Roberts, William Neal; Roman, Jesse; Gangemi, Sebastiano
Lung fibrosis can be observed in systemic sclerosis and in idiopathic pulmonary fibrosis, two disorders where lung involvement carries a poor prognosis. Although much has been learned about the pathogenesis of these conditions, interventions capable of reversing or, at the very least, halting disease progression are not available. Recent studies point to the potential role of micro messenger RNAs (microRNAs) in cancer and tissue fibrogenesis. MicroRNAs are short non-coding RNA sequences (20–23 nucleotides) that are endogenous, evolutionarily conserved and encoded in the genome. By acting on several genes, microRNAs control protein expression. Considering the above, we engaged in a systematic review of the literature in search of overlapping observations implicating microRNAs in the pathogenesis of both idiopathic pulmonary fibrosis (IPF) and systemic sclerosis (SSc). Our objective was to uncover top microRNA candidates for further investigation based on their mechanisms of action and their potential for serving as targets for intervention against lung fibrosis. Our review points to microRNAs of the -29 family, -21-5p and -92a-3p, -26a-5p and let-7d-5p as having distinct and counter-balancing actions related to lung fibrosis. Based on this, we speculate that readjusting the disrupted balance between these microRNAs in lung fibrosis related to SSc and IPF may have therapeutic potential. miR-21-5p and the miR-29 family group cluster in systemic sclerosis and idiopathic pulmonary fibrosis http://ow.ly/D6B030bg2vn